Effectiveness of Mindfulness-Based Group Counseling on Prenatal Anxiety in Primiparous Women - Abbasi, Reyhaneh; Goli, Shahrbanoo; Farjamfar, Maryam; Pourheidari, Mahboobeh; Garkaz, Omid; Paryab, Sahar (Shahroud Journal of Medical Sciences, 2025)
Background: Anxiety during pregnancy is a natural mechanism for coping with maternal concerns that prepares a woman for specific changes and motherhood. However, this natural anxiety can be exacerbated and pathological during this period, and this study aimed to investigate the effect of mindfulness-based group counseling on pregnancy-related anxiety in primiparous women. Methods: This study was a clinical trial on 56 pregnant mothers (30 controls and 30 test subjects) referred to Mashhad health centers. To collect data, a demographic information checklist, Kessler Psychological Distress Scale, and Vandenberg Pregnancy Anxiety Questionnaire were used. Data collection occurred in three time periods: before, immediately, and one month after the intervention. After collection, the data was entered into SPSS18 and analyzed using descriptive and analytical statistics. Results: In this study, the results showed that the average gestational age of the participants in the two groups was 20 weeks. 43.9% of the participants reported their stress level as moderate and 33.3% as severe, and only 10.5% of all had visited a psychiatrist during their lives. Before the intervention, there was no significant difference in the average anxiety score between the two groups, while immediately after the intervention (P-value=0.006) and also one month later (P-value=0.050) a significant decrease in anxiety scores was observed in the intervention group. Conclusions: Given the effectiveness of mindfulness-based group counseling programs in reducing anxiety, planning for implementing these programs during pregnancy should be done.